Epidemiologic evolution of common cutaneous infestations and arthropod bites: A Google Trends analysisCapsule Summary - Thierry Simonart, MD, PhD; Xuân-Lan Lam Hoai, MD; Viviane De Maertelaer, MSc, PhD (Elsevier, 2021)
Background: Common cutaneous infestations and arthropod bites are not reportable conditions in most countries. Their worldwide epidemiologic evolution and distribution are mostly unknown. Objective: To explore the evolution and geographic distribution of common cutaneous infestations and arthropod bites through an analysis of Google Trends. Methods: Search trends from 2004 through March 2021 for common cutaneous infestations and arthropod bites were extracted from Google Trends, quantified, and analyzed. Results: Time series decomposition showed that total search term volume for pubic lice decreased worldwide over the study period, while the interest for ticks, pediculosis, insect bites, scabies, lice, and bed bugs increased (in increasing order). The interest for bed bugs was more pronounced in the former Union of Soviet Socialist Republics countries, interest for lice in Near East and Middle East countries, and interest for pubic lice in South American countries. Internet searches for bed bugs, insect bites, and ticks exhibited the highest seasonal patterns. Limitations: Retrospective analysis limits interpretation. Conclusion: Surveillance systems based on Google Trends may enhance the timeliness of traditional surveillance systems and suggest that, while most cutaneous infestations increase worldwide, pubic lice may be globally declining.